AB0479 Musculoskeletal Manifestations Are Major Determinants of Impaired Quality of Life in Patients with Systemic Lupus Erythematosus. (15th July 2016) - Piga, M.; Congia, M.; Floris, A.; Gabba, A.; Cauli, A.; Mathieu, A.
Abstract : Background: Musculoskeletal (MS) manifestations are among the most frequent expressions of Systemic Lupus Erythematosus (SLE) being present in up to 90–95% of patients during disease course and in 60% of disease flares. They have been associated with impaired quality of life (QoL) in SLE patients. However, the role of different subtype of MS manifestations has not been investigated. Objectives: To investigate the impact of different MS manifestations in SLE patients as major determinants of impaired health related QoL (HRQoL) in SLE. Methods: One hundred twelve consecutive SLE patients (age 47.6± 16.8 years, disease duration 115.5±84.0 months; 6 male) diagnosed according to the 1997 ACR classification criteria were recruited in this cross-sectional study; 87 patients were sub-classified as affected by non-deforming non-erosive arthritis (NDNE), 15 as Jaccoud's arthropathy (JA) and 10 as rhupus syndrome (RS) according to clinical and radiographic features. Thirty-five patients affected with Rheumatoid Arthritis (RA) and 38 healthy controls (HC) were recruited as control groups. HRQoL was evaluated using three validated self-administered questionnaires: the Short Form 36 (SF36) health survey questionnaire, the Heath Assessment Questionnaire (HAQ) and the Fatigue scale v4 (FACIT-4). The search for factors independently associated with low QoL included univariate analyses and stepwise multiple regression models. Explanatory variables tested were: age, disease duration, gender, occupation, arthropathy subtypes, SLEDAI, SLICC damage index, Body Mass Index, arthritis, discoid LE, neuropsychiatric symptoms, active nephritis, depression, fibromyalgia, osteoporosis with fractures, osteonecrosis. Multivariate models were fitted with covariates with p<0.1 to predict outcomes; Bonferroni's corrected p<0.05 was considered significant. Results: SLE patients had worse results (p<0.01) than HC in SF36, HAQ, and FACIT-4. Patients classified as affected by JA and RS had worse results (p<0.01) in SF36, HAQ, and FACIT-4 than patients with NDNE and RA, but no differences were recorded between these two groups. Factors independently associated with lower score in the physical summary components of SF36 were: JA (p=0.01), arthritis (p<0.01) and fibromyalgia (p<0.01). Factors independently associated with lower score in the mental summary components of SF36 were: JA (p<0.01), RS (p<0.01) and fibromyalgia (p<0.01). Factors independently associated with lower HAQ results were: JA (p<0.01), arthritis (p<0.01) and osteoporosis with fracture (p<0.01). Factors independently associated with lower FACIT-4 score were JA (p<0.01) and arthritis (p<0.01). Conclusions: MS manifestations were confirmed as one the major factors associated with lower QoL in patients with SLE. In particular active arthritis, JA and fibromyalgia were associated with low levels of patient's perception in physical function evaluated with the HAQ and SF36, whereas JA and fibromyalgia were determinants of impaired mental health. Active arthritis and JA were associated with increased fatigue perception evaluated with FACIT-4. Disclosure of Interest: None declared